Automation fears: Drivers and solutions. (November 2020) - Ivanov, Stanislav; Kuyumdzhiev, Mihail; Webster, Craig
Abstract: New technologies offer employers the ability to replace tasks done by human labour with those done by machines. There are challenges for both employers and employees, as employers look for strategies for the implementation of automation technologies and employees may have concerns about their employment being threatened by automation technologies. In this research, we analyse data of over 500 Bulgarians to learn about how they perceive the automation of their jobs. The analysis finds that there are segments of the population defined by demographics and attitudes that are more fearful of the automation of their jobs than others. Additionally, we see that attitudes towards the dehumanizing effects of automation, peer-pressure, job automatability, and a person's self-perception of professionalism are the main drivers of the fear of automation. Finally, the paper evaluates respondents' attitudes towards various individual, corporate and social solutions to automation fears. Highlights: The paper discusses the fear of automation. The sample includes 502 respondents from Bulgaria. Dehumanizing effects of automation, peer-pressure, job automatability, and professionalism are the drivers of automation fears. Respondents support mostly individual solutions, followed by corporate and social solutions.